Jababeka Smart Township Super-App Case-Study: Hackathon as a mechanism for Open Innovation - Adhi Setyo Santoso; Chong Mi An; Ronny Juwono (JIE Scientific Journal on Research and Application of Industrial System, 2022)
This case-study articulates the findings and implications of Hackathon which was held as a part of digital literacy training program for the implementation of a Smart City digital platform called “Jababeka Smart Township Super-App”. Firstly, the case-study explores the outputs of the Hackathon and its role as an open innovation mechanism. Secondly, it aims to explore the impact of hackathon on raising the awareness as well as the participants’ willingness to be involved and accept the Smart City implementation. Narrative analysis is employed for the first research objective and descriptive analysis employed for the second research objective where 8 participants are interviewed to provide their accounts on Hackathon and analyzed based on a technology acceptance model (TAM) framework, identifying the Perceived usefulness (PU) and perceived ease of use (PEOU) as the indicators of positive attitude and acceptance towards Smart City implementation. The results indicate that the Super-App as an integrated digital platform can be effectively implemented based on the Open Innovation approach resulting in 30+ community-developed applications, especially as it encourages the community to be the key players in the creation of multi-sided digital platform startups. Finally, Hackathon is found to be a useful mechanism in raising the level of understanding on the concept of Smart City and increase the stakeholders’ acceptance for Smart City implementation.